Potentiation of growth suppression and modulation of multidrug resistance by gamma and beta interferons in MDA-MB-231 breast cancer cell line: IFNs on cancer cells’ growth and resistance - Ghaderi, Pouya; Reza Jalili, Hamid; Mohammadi, Mobin; Rahmani, Mohammad Reza (Cellular and Molecular Biology, 2024)
Multi-drug resistance (MDR) might be acquired by the cancer cells during chemotherapy, and ATP-binding cassette (ABC) transporters play a significant role in MDR. Interferon-γ (IFN-γ) and IFN-β can inhibit cancer cell proliferation; however, the effects and mechanism of these cytokines on the growth and MDR are still unclear. To investigate the effects of IFN-γ and IFN-β, alone or in combination, on viability, resistance, and the expression of ABC transporters of the MDA-MB-231 breast cancer cell line. Using the MDA-MB-231 cell line, we assessed the effects of 20, 100, and 500 IU/ml of IFN-γ and IFN-β, alone or in combination, on cell viability by methyl thiazolyl tetrazolium (MTT) assay; and then we performed the Uptake and Efflux experiment to evaluate the effect of these IFNs on the cell resistance. Then, using quantitative real-time PCR, we evaluated changes in the expression of ABCB1, ABCC1, and ABCG2 mRNA levels. We discovered that IFN-γ and IFN-β might both reduce viability, either alone or in combination. The combination of IFNs also displayed synergistic responses, particularly when utilizing equivalent dosages of 500 or 100 IU/ml. The combination of IFN-γ and IFN-β resulted in a significant increase in Doxorubicin accumulation and down-regulation of the ABCC1 gene at the mRNA level. Our study suggested that equal doses of IFN-γ and IFN-β in combination might result in potentiated responses against cancer, especially, along with chemotherapy agents.